LEGAL ANALYSIS OF THE DETERMINATION OF NATIONAL DISASTER STATUS FROM THE PERSPECTIVE OF CONSTITUTIONAL LAW: A CASE STUDY OF FLOODS IN ACEH AND SUMATERA (Pena Cendekia Insani, 2026)
This study aims to analyze the legal criteria for determining national disaster status in Law Number 24 of 2007 reviewed from the principle of legal certainty and examine the legality and state responsibility for not determining national disaster status in the case of the Aceh-Sumatra flood in 2025. The focus of the research is directed at the problem of the ambiguity of legal norms related to the parameters for determining national disaster status and its implications for the protection of constitutional rights of disaster-affected communities. This study uses a normative legal research method with a statute approach, a conceptual approach, and a case approach. The sources of legal materials consist of primary, secondary, and tertiary legal materials which are analyzed qualitatively through prescriptive-analytical methods with grammatical, systematic, and teleological legal interpretation techniques. The results of the study indicate that the provisions regarding the determination of national disaster status in Law Number 24 of 2007 do not fully fulfill the principle of legal certainty due to the absence of clear quantitative and operational parameters related to the indicators for determining national disaster status. This condition leaves the government with very broad discretionary space, potentially leading to policy inconsistencies and unfairness in state protection for disaster-affected communities. In addition, not determining national disaster status in the case of the 2025 Aceh-Sumatra floods is still normatively possible based on the government's discretionary authority, but from a state responsibility perspective, this policy indicates that the state's constitutional obligations to guarantee the protection of citizens' rights in emergency situations are not yet optimal. The implications of this study emphasize the importance of reformulating disaster management regulations through the development of more objective, transparent, and accountable legal parameters so that the determination of national disaster status has legal certainty and is in line with the principles of the rule of law and the protection of the community's constitutional rights.